Security Analysis and Improvement of Lighweight VANET Authentication Protocol (Case Study : Zhao et al. LVAP) - Sepha Siswantyo (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
VANET is an ad-hoc network implemented on vehicle communication to ensure traffic safety and traffic management efficiency. VANET security is a concern because of various vulnerabilities, especially from authentication criteria that the attacker can exploit. VANET is vulnerable to Sybil attack, entity impersonation, message modification, and identity falsification. Several mechanisms and protocols have been developed to address these vulnerabilities. The design of the VANET authentication protocol also needs to be proven using formal methods to ensure that the protocol meets the required security criteria.  In this research, the security of VANET authentication protocol developed by Zhao et al. was analyzed using the Datta et al. security protocol analysis method. Instead of BAN Logic, the Scyther tool was used to verify security claims and find possible attacks. Our Security analysis results show that Zhao et al.'s protocol does not meet confidentiality and entity authentication criteria. Scyther tool can find attacks on nonce confidentiality and man-in-the-middle attack. Therefore, we modify Zhao et al. protocol by adding signature and session key confirmation to improve its security. Based on analysis results, our modified Zhao et al. authentication protocol met confidentiality and entity authentication criteria. The use of signature and session key confirmation prevents man-in-the-middle attack and protects nonce confidentiality. Therefore, our research concludes that modified Zhao et al. authentication protocol more secure than the original protocol in terms of nonce and session key confidentiality, aliveness, weak agreement, non-injective agreement, and non-injective synchronization.